Exploring the antioxidant, anti-inflammatory and antiallergic potential of Brazilian propolis in monocytes - Fernanda Lopes Conte; Ana Catarina Pereira; Gonçalo Brites; Isabel Ferreira; Ana Cristina Silva; Ana Isabel Sebastião; Patrícia Matos; Cláudia Pereira; Maria Teresa Batista; José Maurício Sforcin; Maria Teresa Cruz (Elsevier, 2022)
Background: Propolis is a bee product used since ancient times due to its diverse biological applications. We aimed to investigate the antioxidant and anti-inflammatory action of Brazilian propolis in THP-1 cells stimulated with 1‐fluoro‐2,4‐dinitrobenzene (DNFB) or lipopolysaccharide (LPS). Methods: Cell viability was assessed by resazurin assay, antioxidant activity was evaluated by DPPH assay, superoxide dismutase (SOD) 1 and 2 activity was evaluated by colorimetric assay. CD86 expression was determined by flow cytometry. IL-1β and HMOX-1 were analysed by Western blot. Results: Propolis did not affect cell viability and exhibited a potent antioxidant activity. Propolis alone induced SOD 1 activity. LPS stimulated SOD2, concomitantly or not with propolis. In the presence of LPS, propolis induced a higher HMOX-1 expression. Propolis inhibited CD86 expression stimulated by DNFB. LPS induced pro-IL-1β expression and propolis did not affect its action. Conclusion: Propolis exhibited an antioxidant action in a cell-free system and in a cell based-model. Propolis exerted an anti-inflammatory/antiallergic action, probably due to its antioxidant activity.